Ultrafast Charge Separation in Bilayer WS2/Graphene Heterostructure Revealed by Time- and Angle-Resolved Photoemission Spectroscopy - Krause, Razvan; Chávez-Cervantes, Mariana; Aeschlimann, Sven; Forti, Stiven; Fabbri, Filippo; Rossi, Antonio; Coletti, Camilla; Cacho, Cephise; Zhang, Yu; Majchrzak, Paulina Ewa; Chapman, Richard T.; Springate, Emma; et al. (Frontiers in Physics, 2021)
Efficient light harvesting devices need to combine strong absorption in the visible spectral range with efficient ultrafast charge separation. These features commonly occur in novel ultimately thin van der Waals heterostructures with type II band alignment. Recently, ultrafast charge separation was also observed in monolayer WS2/graphene heterostructures with type I band alignment. Here we use time- and angle-resolved photoemission spectroscopy to show that ultrafast charge separation also occurs at the interface between bilayer WS2 and graphene indicating that the indirect band gap of bilayer WS2 does not affect the charge transfer to the graphene layer. The microscopic insights gained in the present study will turn out to be useful for the design of novel optoelectronic devices.